KOMUNIKASI INTERPERSONAL DI DINAS PENDIDIKAN PROVINSI SUMATERA BARAT - Jayanti Syahfitri; Adi , Nelfia (Journal of Practice Learning and Educational Development, 2023)
This research is motivated by problems related to Interpersonal Communication which is still not good at the Education Office of West Sumatra Province. The formulation of the problem in this study is How is Interpersonal Communication between leaders and employees, employees and leaders and between fellow employees at the Education Office of West Sumatra Province. This study aims to explore information about Interpersonal Communication at the Education Office of West Sumatra Province in terms of aspects of trust, including empathy and positive attitude. This type of research is descriptive quantitative. The study population was all employees at the West Sumatra Province Education Office, totaling 165 people. Take a sample of 132 people using a proportional stratified random sampling technique. The data collection instrument was a Likert Scale Questionnaire model with five answer choices, namely always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). This research questionnaire was tested on 30 people and processed using the SPSS 26.0.0 program, the results of the instrument were declared valid and reliable. Data analysis techniques use the average formula (mean). The results showed that interpersonal communication in aspects 1) Interpersonal Communication between leaders and employees from trust, inclusion, empathy and a positive attitude with an average score of 4.23 is in the good category, 2) Interpersonal Communication between Employees and leaders from trust, causes , empathy and a positive attitude with an average score of 4.25 are in the good category, 3) Interpersonal communication between fellow employees of trust, cause, empathy and a positive attitude with an average score of 3.76 is in the good category. Thus it can be concluded that Interpersonal Communication at the Education Office of West Sumatra Province is in the good category with an average score of 4.08. Based on these results, the authors suggest that Interpersonal Communication at the Education Office of West Sumatra Province is maintained and needs to be improved again so as to create effective Interpersonal Communication between employees and leaders and between employees.